Overcoming challenges of supply chain management: Contributions from Blockchain technology - Tokkozhina, Ulpan (2022)
The interest towards digital solutions for supply chain management (SCM) grows constantly, and one of potential technologies that seems promising to bring SCM improvements is blockchain technology (BCT). The purpose of this research is to investigate the main challenges that supply chains (SCs) face nowadays and assess the ability of BCT in serving SCs and overcoming potential challenges with its technological features. In pursuing its purpose, this research is developed around three studies and applies a variety of methodological approaches. Study 1 introduced three dimensions of BCT implementation in SCM using a systematic literature review. Interrelated and overlapping areas of ‘operations and processes’, ‘supply chain relationships’, and ‘innovation and data access’ were detected, which found to be leading to synergetic and counter-synergetic effects in the SC. Study 2 explored international views of early adopters of BCT in SC practices, as well as technology consultants through semi-structured interviews. It revealed the joint views of both groups: BCT holds the ability to speed up SC processes through decentralisation, thus decreasing human errors and reducing paperwork. However, technology consultants highlight the need to increase BCT awareness levels to reduce misconceptions and motivate initiatives towards open-access networks. Study 3 investigated a single multi-tier SC that adopted BCT through a mixed-method approach, revealing differences in motivation for BCT adoption across tiers, and showing a clear interest of final consumers in obtaining products’ traceability information, leading to higher purchase intentions. The research ends with an integrated discussion of the contributions from each of the three studies.